CHARACTERISTICS OF ASBUTON'S COLD PAVING HOT MIX (CPHMA) BASED ON MARSHALL TEST (FSTPT Indonesia, 2023)
The purpose of this study was to obtain the characteristics of the Cold Paving Hot Mix Asbuton (CPHMA) mixture based on the Marshall test. The presentation of data analysis is presented after all research processes in the form of testing the mixed Marshall characteristics have been achieved or have been completed. The results of the examination of the physical properties of the material show results that meet the general specifications of 2018 revision 2. Based on the characteristics of the asphalt mixture with two types of mixtures, the values of the properties of the mixture based on the Marshall test, the characteristic values of the CPHMA mixture are 6.1% asphalt content, 6.6% VIM, VMA 29.6%, VFB 78.0%, stability 619 kg, melt (flow) 5.0 mm, and 73.2%. While the characteristics of the HRS-WC mixture are asphalt content 6.9%, VIM 5.0%, VMA 19.1%, VFB 73.6%, stability 1159 kg, MQ 288kg/mm, and residual stability 91.7%. The quality of the CPHMA mixture from the results of the characteristic test based on the Marshall test meets the required specifications and the CPHMA mixture can encourage the independence of the National asphalt based on Buton asphalt. ABSTRAK Tujuan dari penelitian ini adalah untuk mendapatkan karakteristik campuran Cold Paving Hot Mix Asbuton (CPHMA) berdasarkan uji Marshall. Penyajian analisis data disajikan setelah semua proses penelitian berupa pengujian karakteristik campuran Marshall telah tercapai atau telah selesai. Hasil pemeriksaan sifat fisis material menunjukkan hasil yang memenuhi spesifikasi umum tahun 2018 revisi 2. Berdasarkan karakteristik campuran aspal dengan dua jenis campuran, maka nilai sifat campuran berdasarkan Marshall pengujian, nilai karakteristik campuran CPHMA adalah kadar aspal 6,1%, VIM 6,6%, VMA 29,6%, VFB 78,0%, stabilitas 619 kg, leleh (flow) 5,0 mm, dan 73,2%. Sedangkan karakteristik campuran HRS-WC adalah kadar aspal 6,9%, VIM 5,0%, VMA 19,1%, VFB 73,6%, stabilitas 1159 kg, MQ 288kg/mm, dan stabilitas residu 91,7%. Mutu campuran CPHMA dari hasil uji karakteristik berdasarkan uji Marshall memenuhi spesifikasi yang dipersyaratkan dan campuran CPHMA dapat mendorong kemandirian aspal Nasional berbasis aspal Buton.